2012
DOI: 10.1007/978-94-007-4572-8_15
|View full text |Cite
|
Sign up to set email alerts
|

PCNA Structure and Function: Insights from Structures of PCNA Complexes and Post-translationally Modified PCNA

Abstract: Proliferating cell nuclear antigen (PCNA), the eukaryotic DNA sliding clamp, forms a ring-shaped homo-trimer that encircles double-stranded DNA. This protein is best known for its ability to confer high processivity to replicative DNA polymerases. However, it does far more than this, because it forms a mobile platform on the DNA that recruits many of the proteins involved in DNA replication, repair, and recombination to replication forks. X-ray crystal structures of PCNA bound to PCNA-binding proteins have pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 55 publications
1
75
0
5
Order By: Relevance
“…The canonical PIP motif is a weak consensus sequence of eight amino acids QXXhXXaa where ‘h’ is a moderately hydrophobic amino acid and ‘a’ is an aromatic residue (9). The PIP-containing proteins bind to the PCNA trimer in a small hydrophobic cavity near the IDCL [reviewed in: (10)].…”
Section: Introductionmentioning
confidence: 99%
“…The canonical PIP motif is a weak consensus sequence of eight amino acids QXXhXXaa where ‘h’ is a moderately hydrophobic amino acid and ‘a’ is an aromatic residue (9). The PIP-containing proteins bind to the PCNA trimer in a small hydrophobic cavity near the IDCL [reviewed in: (10)].…”
Section: Introductionmentioning
confidence: 99%
“…Genotoxicity or nongenotoxicity stress signals, such as DNA damage, expression of abnormal growth signals, chemical therapeutic drugs treatment, ultraviolet ray can promote protein kinases to react with some kinds of amino acids located at p53 Nterminal (Ser6, Ser9, Ser15, Ser20, Ser28) or C-terminal and make those amino acids phosphorylated by protein kinases, such as ATM, CK1 and Chk2. Ultimately, the cell growth inhibition, apoptosis, adaption for DNA damage and survival [14] will occur in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from our lab demonstrated that assembly/disassembly of a pol δ holoenzyme and continuous DNA synthesis by a pol δ holoenzyme are both independent of PCNA monoubiquitination (Hedglin et al, 2016). The ubiquitin moieties attached to PCNA do not alter the conformation of the sliding clamp ring (Dieckman et al, 2012) nor do they shelter the region of PCNA that interacts with DNA pols (Tsutakawa et al, 2011, 2015). Hence, monoubiquitination of PCNA is not envisioned to have any effect on DNA synthesis by a pol ε holoenzyme on a leading strand template.…”
Section: Discussionmentioning
confidence: 99%